2004
DOI: 10.1111/j.0001-5172.2004.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remifentanil on intracranial pressure and cerebral blood flow velocity in patients with head trauma

Abstract: These data suggest that remifentanil can be used for on-top analgesia in head trauma patients without adverse effects on cerebrovascular haemodynamics, cerebral perfusion pressure or intracranial pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…In patients with traumatic brain injury, it has been demonstrated that remifentanil has no significant changes in systematic and cerebral haemodynamics, such as intracranial pressure, mean blood pressure (BP), cerebral perfusion pressure and cerebral blood flow velocity 22. Several studies also compared remifentanil with fentanyl or morphine as an analgesic in neurological ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with traumatic brain injury, it has been demonstrated that remifentanil has no significant changes in systematic and cerebral haemodynamics, such as intracranial pressure, mean blood pressure (BP), cerebral perfusion pressure and cerebral blood flow velocity 22. Several studies also compared remifentanil with fentanyl or morphine as an analgesic in neurological ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…Remifentanil (bolus of 0.5 μg/kg, followed by a continuous infusion 0.25 μg/kg/min for 20 min) can also be used for on‐top analgesia in head trauma patients without adverse effects on cerebrovascular hemodynamics and CPP (43).…”
Section: Cerebral Perfusion Pressure (Cpp)mentioning
confidence: 99%
“…Different studies, carried out to investigate the effects of opioids, both alone and in combination with other anesthetic agents, demonstrated how these drugs could affect cerebral hemodynamics with consequent increases in ICP and reduction in CBF (69).…”
Section: Anesthetic Agentsmentioning
confidence: 99%